2022
DOI: 10.4274/tjo.galenos.2021.66168
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye and Meibomian Gland Dysfunction in Neovascular Age-Related Macular Degeneration Patients Treated with Intravitreal Injections

Abstract: Objectives: To determine if patients treated with multiple intravitreal injections for neovascular age-related macular degeneration are more likely to suffer from dry eye and meibomian gland dysfunction. Materials and Methods: Sixty eyes of 30 patients were enrolled. One eye of each patient was treated with multiple monthly intravitreal injections for neovascular AMD (Group 1) and the fellow healthy eye received no treatment (Group 2). The presence of dry eye was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…However, there are limited clinical studies on this procedure, which has been widely used in ophthalmology practice. [9][10][11]19,20 In this study, the injection eyes and fellow eyes of patients with AMD with unilateral injection were compared. Thus, the effect of confounding factors that could affect the results, such as systemic disease, age, and sex, was minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are limited clinical studies on this procedure, which has been widely used in ophthalmology practice. [9][10][11]19,20 In this study, the injection eyes and fellow eyes of patients with AMD with unilateral injection were compared. Thus, the effect of confounding factors that could affect the results, such as systemic disease, age, and sex, was minimized.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited clinical studies on this procedure, which has been widely used in ophthalmology practice. 9–11,19,20…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the efficacy of 0.6% povidone-iodine (PVI) in treating ocular surface diseases, improving signs and symptoms in patients with dry eye disease (DED) and Meibomian gland dysfunction (MGD) [ 17 ]. PVI is an antiseptic with several properties, such as immediate broad-spectrum activity against different types of bacteria, with no reported microbial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PVI presents effective anti-inflammatory activity as well as great efficacy in wound healing. It has been shown to be safe and very well tolerated [ 17 ]. Although PVI is generally safe, some complications have been described in the literature, such as allergic reactions, ocular irritation, post-operative eye pain, and corneal toxicity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%